First studies of the diffuse X-ray emission in the Large Magellanic Cloud with eROSITA - Sasaki, Manami; Knies, Jonathan; Haberl, Frank; Maitra, Chandreyee; Kerp, Juergen; Bykov, Andrei M.; Dennerl, Konrad; Filipovic, Miroslav D.; Freyberg, Michael; Koribalski, Barbel S.; Points, Sean; Staveley-Smith, Lister (Astronomy & Astrophysics, 2022)
Context. In the first months after its launch in July 2019, the extended Roentgen Survey with an Imaging Telescope Array (eROSITA) on board Spektrum-Roentgen-Gamma performed long-exposure observations in the regions around supernova (SN) 1987A and super-nova remnant (SNR) N132D in the Large Magellanic Cloud (LMC). Aims. We analysed the distribution and the spectrum of the diffuse X-ray emission in the observed fields to determine the physical properties of the hot phase of the interstellar medium (ISM). Methods. Spectral extraction regions were defined using the Voronoi tessellation method. The spectra were fit with a combination of thermal and non-thermal emission models. The eROSITA data are complemented by newly derived column density maps for the Milky Way and the LMC, 888 MHz radio continuum map from the Australian Square Kilometer Array Pathfinder, and optical images of the Magellanic Cloud Emission Line Survey. Results. We detect significant emission from thermal plasma with kT = 0.2 keV in all the regions. There is also an additional higher- temperature emission component from a plasma with kT approximate to 0.7 keV. The surface brightness of this component is one order of magnitude lower than that of the lower-temperature component. In addition, non-thermal X-ray emission is significantly detected in the superbubble 30 Dor C. The absorbing column density N-H in the LMC derived from the analysis of the X-ray spectra taken with eROSITA is consistent with the N-H obtained from the emission of the cold medium over the entire area. Neon abundance is enhanced in the regions in and around 30 Dor and SN 1987A, indicating that the ISM has been chemically enriched by the young stellar population. In the centre of 30 Dor, there are two bright extended X-ray sources, which coincide with the stellar cluster RMC 136 and the Wolf-Rayet stars RMC 139 and RMC 140. For both regions the emission is best modelled with a high-temperature (kT > 1 keV) non-equilibrium ionisation plasma emission and a non-thermal component with a photon index of Gamma = 1.3. In addition, we detect an extended X-ray source at the position of the optical SNR candidate J0529-7004 with thermal emission, and thus confirm its classification as an SNR. Conclusions. Using data from the early observations of the regions around SN 1987A and SNR N132D with eROSITA we confirm that there is thermal interstellar plasma in the entire observed field. eROSITA with its large field of view and high sensitivity at lower X-ray energies allows us for the first time to carry out a detailed study of the ISM at high energies consistently over a large region in the LMC. We thus measure the properties of the interstellar plasma and the distribution of non-thermal particles and derive the column density of the cold matter on the line of sight.
CRIS-Team WoS Importer:2022-06-17